De norske stavkirkenes svalganger i et internasjonalt perspektiv. (3rd April 2019) - Andersen, Håkon A.
Summary: A large number of Norwegian stave churches with a portico were built in the period 1150–1250. This article examines these porticoes in an international context. From the same period, one can find parallels in a large number of smaller, European stone churches, predominantly in France and northern Spain. Norwegian and European churches have several functions in common. It would likely be relevant to look at the porticoes in light of developments in church history.